2014
DOI: 10.1111/sltb.12125
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Examination of the Interpersonal‐Psychological Theory of Suicidal Behavior Among Psychiatric Adolescent Inpatients

Abstract: The challenge of identifying suicide risk in adolescents, and particularly among high-risk subgroups such as adolescent inpatients, calls for further study of models of suicidal behavior that could meaningfully aid in the prediction of risk. This study examined how well the Interpersonal-Psychological Theory of Suicidal Behavior (IPTS)—with its constructs of thwarted belongingness (TB), perceived burdensomeness (PB), and an acquired capability (AC) for lethal self-injury—predicts suicide attempts among adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 52 publications
8
58
0
1
Order By: Relevance
“…We found that perceived burdensomeness mediated the associations of two important variables, depression and hopelessness, with suicidal ideation. The stronger influence of perceived burdensomeness in comparison to thwarted belongingness is consistent with previous reports suggesting that the former may be the more strongly weighted of the two (Czyz et al 2014).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…We found that perceived burdensomeness mediated the associations of two important variables, depression and hopelessness, with suicidal ideation. The stronger influence of perceived burdensomeness in comparison to thwarted belongingness is consistent with previous reports suggesting that the former may be the more strongly weighted of the two (Czyz et al 2014).…”
Section: Discussionsupporting
confidence: 80%
“…However, few studies have utilized clinical samples (Joiner et al 2009) or specifically adolescent clinical samples (exceptions are Czyz et al 2014;Klonsky et al 2013;Liu et al 2014;Nock et al 2006;Prinstein et al 2008;Sheftall et al 2013). Relative to studies on acquired capability for suicide, there are fewer studies focusing on thwarted belongingness and perceived burdensomeness with adolescent clinical samples in the IPTS literature.…”
Section: Shortcomings In Literature Guiding This Studymentioning
confidence: 91%
See 3 more Smart Citations